(untitled) (Bangladesh Journal of Medical Science, 2016)
Objectives: Evidence suggests that inflammation and dyslipideamia play a key role in the pathogenesis of coronary artery disease (CAD). High sensitivity C-reactive protein (hs- CRP) is a sensitive marker of inflammation. We attempted to evaluate the contribution of dyslipidaemia and inflammation in CAD. Materials and methods: Three hundred and nine males (103 with myocardial infarction - MI, 103 with established CAD, 103 healthy controls) were studied. The serum hs-CRP, lipids and plasma glucose were determined. Results: Baseline mean hs-CRP levels in patients with established CAD and MI were significantly higher compared to controls (3.4 ± 1.62 VS. 1.70 ± 0.60 mg/L, p = 0.001) (3.7 ± 0.65 VS. 1.70 ± 0.60 mg/L, p = 0.001). A significant negative correlation observed between hs-CRP and HDL-Ch (r = -0.359, p = 0.001). Conclusion: Inflammation (which was reflected by elevated hs-CRP) and dyslipidamia were associated with coronary artery disease. Bangladesh Journal of Medical Science Vol.15(1) 2016 p.44-50